A Case Study on How Allocative Efficiency Analysis Supported by Mathematical Modelling Changed HIV Investment in Sudan - World Bank (World Bank, Washington, DC, 2016)
This brief presents a real-life example of how a group of government decision-makers, programme managers, researchers and development partners worked together to improve the allocation of HIV resources in Sudan and thereby better address the HIV objectives that the country strives to achieve. The initial modelling analysis showed that by reallocating funds towards antiretroviral treatment (ART) and prevention programmes in Sudan, 37 percent of new HIV infections could be averted with the same amount of funding. These allocations combined with additional technical efficiency gains would allow for increasing ART coverage from 6 percent in 2013 to 34 percent in 2017, and more than double programme coverage for key populations. The reallocations in the 2015 to 2017 HIV budget for the national response are projected to avert an additional 3,200 new infections and 1,100 deaths in these three years compared to initially planned allocations.The reallocations were achieved through a rigorous HIV allocative efficiency analysis and evidence-informed policy process, conducted by a multi-disciplinary team of national and international partners working for the common goal to make Sudan’s HIV response more manageable and sustainable. The case study discusses process and outcomes of this effort. It also offers some reflections on the application of mathematical modelling to strengthening decision-making of finite HIV resources, and some lessons learned about how to go ‘beyond modelling’ to application of modelled allocative efficiency improvements to improving actual budget allocations for better health outcomes.